2005
DOI: 10.1007/s10750-004-8333-y
|View full text |Cite
|
Sign up to set email alerts
|

The structure of diatom assemblages associated with Cladophora and sediments in a highland stream in Kenya

Abstract: Epiphytic and epipelic diatoms were collected from six sites in the Njoro River, Kenya, during the dry season between January and March 1997. Diatom assemblage descriptors, such as composition, distribution, species diversity as well as diatom habitat preferences and growth-form guilds were considered. Human activities in the Njoro River watershed included small-scale livestock keeping, subsistence farming, horticultural farming, and canning activities; all these activities have polluted the river. The diatom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…However, these aspects in microbial communities are poorly know especially in extreme environments. In New Zealand, according to [7] 144 taxa in thermal and mixed thermal/non-thermal waters were dominated by the genera Nitzschia (24), Pinnularia (16), Navicula (10), and Surirella (7). In this work, we reported 102 taxa in thermal and mixed thermal/non-thermal waters dominated by the genera Nitzschia (16), Navicula (13), Gomphonema (7), Planothidium (6), and Denticula (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these aspects in microbial communities are poorly know especially in extreme environments. In New Zealand, according to [7] 144 taxa in thermal and mixed thermal/non-thermal waters were dominated by the genera Nitzschia (24), Pinnularia (16), Navicula (10), and Surirella (7). In this work, we reported 102 taxa in thermal and mixed thermal/non-thermal waters dominated by the genera Nitzschia (16), Navicula (13), Gomphonema (7), Planothidium (6), and Denticula (5).…”
Section: Discussionmentioning
confidence: 99%
“…Angel [10]. Other diatom floras were described in hot-spring systems of Iceland, New Zealand, and Kenya [6].…”
Section: Introductionmentioning
confidence: 99%
“…Passy et al (1999) showed that compared with epiphyton, epilithic diatoms had the lowest correlation with ionic strength and eutrophication. Tests performed on epipelic and epiphytic diatoms in Kenyan rivers (Mpawenayo & Mathooko, 2005) showed a decrease of adnate diatoms in both habitats when pollution increased. One way to homogenize the substrates effect is to use artificial substrates (Maznah & Mansor, 2002;Dela-Cruz et al, 2006;Duong et al, 2006;Ndiritu et al, 2006), although Fisher & Dunbar (2007) showed that diatom communities and biomass between natural and artificial substrates were quite different.…”
Section: Biotic Diatom Indices (Group Of Papers #4)mentioning
confidence: 97%
“…In North America, it is a frequently detected in streams (Brian 2000;Hill et al 2003;Johansen et al 2007;Potapova and Charles 2007;Ratnasabapathy and Deason 1977;Stoermer et al 1999;Waite et al 2006;Wunsam et al 2002), and it is also found in the marine intertidal zone at the water's edge or on river estuaries (Patrick 1994). F. weinholdii was also observed in Cuba (Marvan unpublished), in inland waters of Australia (Day et al 1995), and in a highland stream in Kenya (Mpawenayo and Mathooko 2005 Non-native distribution in the world: The nonnative distribution of F. weinholdii is unknown.…”
Section: Frustulia Weinholdii Hustedt 1937mentioning
confidence: 97%